Integration of multiple-linear and tumbling kinematics into self-piercing riveting - Holtkamp, Pia Katharina; Wituschek, Simon; Lechner, Michael; Meschut, Gerson (MATEC Web of Conferences)
Conventional mechanical joining processes are typically rigid in their tool systems and can only react to changing process and disturbance variables to a limited extent. At the same time, various industries are increasingly trending towards multi-material systems consisting of parts with varying geometric and mechanical properties. Due to the varying properties, rigid mechanical joining processes require sampling procedures and periodic changes of tool components or auxiliary joining parts. Consequently, research is focusing on versatile mechanical joining processes that allow increased control by modifying the process parameters. Two processes based on self-piercing riveting can achieve a significant increase in process influence possibilities through a multi-linear actuator as versatile self-piercing riveting (V-SPR) and a tumbling superimposed actuator as tumbling self-piercing riveting (T-SPR). Initial research into V-SPR has shown that this process can be used to achieve a higher variation in overall package thickness by adapting the rivet geometry and using multiple linear actuators. The T-SPR process also enables increased material flow control by means of targeted compression of the rivet using the tumbling actuator, thereby extending the range of joints that can be manufactured. Based on these two processes, a combination of the two mechanisms of action is to be developed.

Non-destructive testing in versatile joining processes - Lechner, M.; Borgert, Thomas; Busch, Matthias; Harms, A.; Holtkamp, Pia Katharina; Römisch, D.; Wituschek, Simon; Kappe, Fabian (Materials Research Proceedings)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT's application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysis.

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
The increasing significance of ecological responsibility, stricter political regulations and economic objectives are driving innovation in research fields such as lightweight construction. One of the most important popular methods is the use of multi-material systems. Due to the different geometric and mechanical properties of the various materials used, resource efficient applications and utilizations are possible. Great challenges arise for the joining processes to realize these multi-material systems, since conventional joining processes reach their limits. In the field of mechanical joining processes, there are continuously new approaches, such as superimposing the punch in a self-piercing riveting process with a tumbling kinematic, to increase the number of adaptable process parameters and enhance the process control. Through various preliminary tests, a good understanding of the process has been developed, which allows to directly control the geometric joint parameters by configuring the tumbling strategy. A major challenge, particularly with regard to future industrial applications, is the process time, which is comparatively high due to the tumbling kinematics. In the investigations, a reduction of approximately 90% of the process time is targeted by adapting the joining and tumbling strategy. Therefore, the correlation of the traverse velocity and the tumbling velocity are examined in a gradual series of experiments. To represent realistic applications, the experiments are carried out with a dual-phase steel and a precipitation-hardening aluminum alloy. For identifying the influence of the process parameters on the joining process, a constant rivet–die combination is applied. Further, the examination of force–displacement curves is conducted. Moreover, the determination of geometric joint parameters is reliant upon macrographs to assess the influence of the joining time on the geometric joint formation. The test results show that a significant increase in joining speed with a resulting reduction in process time is feasible. Although the joining properties are affected, reliable joining is possible. In particular, the shaft thickness of the rivet is influenced by the varying proportion of the tumbling process in the joining operation and increases with higher joining speeds.

Investigation on the load-bearing capacity and joint formation of hybrid functional components joined by orbital forming - Hetzel, A.; Wituschek, Simon; Römisch, D.; Sippel, F.; Lechner, M.; Merklein, M. (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Increasing material costs, decreasing availability, and ever-higher demands on environmental compatibility and complexity require new strategies in the development and production of functional components. Consequently, a combined approach from the areas of design, material science, and manufacturing is mandatory, in order to meet the requirements. Reducing the number of parts, using lightweight materials and applying hybrid components with a multimaterial mix are possible solutions. Nevertheless, conventional joining operations like welding or riveting are reaching their limits in terms of material utilization, load-bearing capacity as well as versatility of the process. Thus, innovative and versatile joining by forming operations and process combinations are focus of current research. In this context, the innovative process of orbital forming had been investigated as a joining by forming operation to manufacture load-adapted hybrid functional components. By tilting of one tool component during the process, a radial material flow is generated, allowing the crimping of the two joining partners. Nevertheless, the load-bearing capacity in axial direction could be identified as limiting factor for a possible application. Therefore, the aim of this investigation is the development of a fundamental process understanding on the influence of a novel geometrical adaption of the joint on the resulting load bearing capacity. The influence of varying geometrical proportions of the joint on the quality is evaluated, considering the form filling, the geometrical properties of the components as well as the maximum transmittable axial load. As joining partners, the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 2.0 mm are used.